2019
DOI: 10.1101/733766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Related enteric viruses have different requirements for host microbiota in mice

Abstract: 24Accumulating evidence suggests that intestinal bacteria promote enteric virus infection 25 in mice. For example, previous work demonstrated that antibiotic treatment of mice prior 26 to oral infection with poliovirus reduced viral replication and pathogenesis. Here we 27 examined the effect of antibiotic treatment on infection with coxsackievirus B3 (CVB3), a 28 picornavirus closely related to poliovirus. We treated mice with a mixture of five 29 antibiotics to deplete host microbiota and examined CVB3 re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In humans and mice, it has been shown that the stability and survival of certain viruses in the gut are enhanced when the viral particles are attached to bacterial components. For instance, gut bacteria that express histo-blood group antigens stabilize norovirus in humans 20 , while bacterial N-acetylglucosamine and lipopolysaccharides (LPS) have a similar effect for poliovirus in mice 21 , 22 . Furthermore, the gut microbiota can have effects on remote parts of the body, and, for example, can act on the respiratory system to influence the disease severity of influenza or the vaccine response.…”
Section: Introductionmentioning
confidence: 99%
“…In humans and mice, it has been shown that the stability and survival of certain viruses in the gut are enhanced when the viral particles are attached to bacterial components. For instance, gut bacteria that express histo-blood group antigens stabilize norovirus in humans 20 , while bacterial N-acetylglucosamine and lipopolysaccharides (LPS) have a similar effect for poliovirus in mice 21 , 22 . Furthermore, the gut microbiota can have effects on remote parts of the body, and, for example, can act on the respiratory system to influence the disease severity of influenza or the vaccine response.…”
Section: Introductionmentioning
confidence: 99%